PGRI DKI Jakarta's Struggle For The Welfare Of Honorary Teachers In Jakarta At The Elementary Education Level (2005-2018) - Nurbaity, Nurbaity; Handayani , Yeni; Noviyanti, Rani (International Humanity Advance, Business & Sciences, 2025)
Teachers (educators) deliver information, knowledge and learning materials. Teachers are the key to success in achieving educational goals. The role of teachers is vital because they have the task of achieving goals from academic institutions, curriculum, and even from their students. No exception is the honorary teacher who, in this study, will be discussed at the Elementary Education level, including the Elementary School Level. PGRI is an organisation that accommodates the interests of teachers whose birth date, November 24, 1945, has been used as Teachers' Day in Indonesia. One of the roles of PGRI as a professional organisation is to have a central role in improving teacher competence and carrying out the primary responsibility in transforming students' science, technology, and arts. Based on its established vision and mission, PGRI always fights for the fundamental rights of teachers (educators), including professional allowances received by educators and the welfare provided. The writing of this article uses a historical method that includes four steps of activity, including heuristic and the step of collecting sources, some of which are obtained from the Kompas newspaper, PGRI organisation books, and interviews. The second stage is criticism, consisting of internal and external criticism. The third stage is interpretation, and the last is writing history or historiography. The findings of this study are that there are still honorary teachers at the Elementary Education Unit Level. PGRI, even until now, continues to fight to defend the interests of educators related to professionalism, protection of human rights, and the welfare of educators, especially honorary teachers. PGRI continues to advance in facing challenges, even though this organisation often faces trials. The struggle carried out by PGRI is through parliamentary channels (discussions and hearings) until the agreement on the formation of the 2005 Teachers and Lecturers Law, as well as the media and demonstration movements.